2016
DOI: 10.3947/ic.2016.48.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Effects of Pneumococcal Conjugate Vaccines in National Immunization Programs for Children on Adult Pneumococcal Disease

Abstract: The pneumococcal conjugate vaccine (PCV) was developed to overcome the limitations of the pneumococcal polysaccharide vaccine, which produces poor immunogenicity in infants younger than 2 years. As many countries have included PCVs in national immunization programs for children, the incidence of invasive pneumococcal disease caused by vaccine type Streptococcus pneumoniae has declined markedly, not only among the vaccinated pediatric population, but also among unvaccinated adults. In this review, we present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 56 publications
(97 reference statements)
0
22
0
1
Order By: Relevance
“…35 By reducing the carriage of S. pneumoniae and transmission to contacts, there also has been a concordant decline in the incidence of IPD among the non-vaccinated population. 36 As other published economic have reported, 15,31 the herd effects of vaccinations have a substantial impact on the economic outcomes of PCV-13. When the herd effect was included, our model outputs found that the ICERs of a PCV-13 vaccination program Figure 2.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…35 By reducing the carriage of S. pneumoniae and transmission to contacts, there also has been a concordant decline in the incidence of IPD among the non-vaccinated population. 36 As other published economic have reported, 15,31 the herd effects of vaccinations have a substantial impact on the economic outcomes of PCV-13. When the herd effect was included, our model outputs found that the ICERs of a PCV-13 vaccination program Figure 2.…”
Section: Discussionmentioning
confidence: 95%
“…over a no vaccination strategy become more favorable (decreasing nearly 30%) in a base-case analysis, and the probabilities of cost-effectiveness increased over 50% in PSA compared to the scenario without the herd effect. Although the herd effect PCV data are increasing, 36 there is still no confirmed evidence of the impact of herd immunity of universal PCVs vaccination in East Asia, where the environmental risk factors, family structures, mixing patterns, and culture are vastly different compared with Western regions. Therefore, it is still uncertain whether to similar herd effects expand to the whole population, as described in published Western reports.…”
Section: Discussionmentioning
confidence: 99%
“…37 Real world observational data indicate that the incidence of IPD has declined among both vaccinated and non-vaccinated populations due to indirect effects. 38 Conversely, the implementation of PCVs can also lead to undesired, negative population effects such as serotype replacement. 39 This further complicates the estimation of the full value of a PCV program.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus pneumoniae is one of the leading causes of otitits media, bacterial meningitis, and community-acquired pneumonia that may be fatal in children under the age of five [11] . Penicillin non-susceptibility in pneumococcus strains has been reported from all WHO regions and rates exceeding 50% have been reported in some regions ( Table 2).…”
Section: The Current State Of Global Antimicrobial Resistancementioning
confidence: 99%